2018
DOI: 10.1016/j.cam.2018.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Functional approach to the error control in adaptive IgA schemes for elliptic boundary value problems

Abstract: This work presents a numerical study of functional type a posteriori error estimates for IgA approximation schemes in the context of elliptic boundary-value problems. Along with the detailed discussion of the most crucial properties of such estimates, we present the algorithm of a reliable solution approximation together with the scheme of an efficient a posteriori error bound generation. In this approach, we take advantage of B-(THB-) spline's high smoothness for the auxiliary vector function reconstruction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Other exciting directions of research are provided in the following recent contributions including space-time analysis, as well as functional-type error estimates for isogeometric analysis, see Langer et al (2016); Matculevich (2018); Langer et al (2019).…”
Section: Isogeometric Analysismentioning
confidence: 99%
“…Other exciting directions of research are provided in the following recent contributions including space-time analysis, as well as functional-type error estimates for isogeometric analysis, see Langer et al (2016); Matculevich (2018); Langer et al (2019).…”
Section: Isogeometric Analysismentioning
confidence: 99%
“…The optimal value for β reads as β := C F m I eq / m I d . According to numerical results obtained in [34,47,43], the most efficient majorant reconstruction is obtained with spline degree q p. At the same time, the approximation u h is reconstructed on the mesh K h , whereas a coarser mesh K Mh , M ∈ N + , is used to recover y h . This helps to minimise the number of d.o.f.…”
Section: A Posteriori Error Estimates and Numerical Experimentsmentioning
confidence: 99%
“…By exploiting the universality and efficiency of these error estimates as well as taking an advantage of smoothness of the IgA approximations, we aim at constructing fast fully adaptive space-time methods that could tackle complicated problems inspired by industrial applications. These two techniques were already combined in application to elliptic problems in [34] and [47] using tensor-based splines and THB-splines [23,24,22], respectively. Both papers confirmed that the majorants provide not only reliable and efficient upper bounds of the total energy error but a quantitatively sharp indicator of local element-wise errors.…”
Section: Introductionmentioning
confidence: 99%
“…In the spirit of [Rep99,Rep00a,Rep00b], the works [KT15a, KT15b,Mat18] present guaranteed fully computable upper bounds of the approximation error for tensor-product splines and hierarchical splines, respectively. A second estimate is also derived, giving a lower bound of the error.…”
Section: Introductionmentioning
confidence: 99%